Thrombin generation in newly diagnosed multiple myeloma during the first three cycles of treatment: An observational cohort study. Issue 1 (13th December 2018) - Chalayer, Emilie; Tardy‐Poncet, Brigitte; Karlin, Lionel; Chapelle, Céline; Montmartin, Aurélie; Piot, Michèle; Guyotat, Denis; Collet, Philippe; Lecompte, Thomas; Tardy, Bernard
Abstract: Background: Multiple myeloma (MM) is associated with a high risk of thrombosis, particularly during the first months of treatment including immunomodulatory drugs (IMiDs). There is no consensus on prevention of thromboembolic risk in patients with de novo MM, and identification of patients requiring anticoagulant thromboprophylaxis remains challenging. Evaluating coagulability by an in vitro thrombin generation (TG) test might be a way of identifying such patients. Objective: To determine whether TG assessment could reveal an increase in coagulability during the first three chemotherapy cycles. Methods: This prospective and longitudinal observational study included patients newly diagnosed with MM. TG was determined in platelet‐rich and platelet‐poor plasma using calibrated automated thrombography with a low tissue factor (TF) concentration. Results: Seventy‐one patients were enrolled, allowing TG analysis during 213 chemotherapy cycles. TG remained unchanged throughout follow‐up irrespective of treatment regimen, but values determined before cycles 2 and 3 were significantly higher in patients receiving iMiDs‐containing regimens. No association was found between TG and its changes and thrombosis occurrence during follow‐up: venous thrombosis in eight patients; no cardiovascular event. A significantly (87%) lower risk of venous thrombosis was observed in patients receiving prophylaxis with a low‐molecular‐weight heparin (LMWH; OR: 0.13 (95% CI: 0.02‐0.76). Neither bortezomib‐ nor dexamethasone‐containing regimens were associated with thrombotic risk. Changes in TG, as studied, were not associated with thrombotic events. Conclusions: The only factor associated with a reduction in early thrombotic risk was prophylaxis with LMWH. The issue of how to identify patients requiring prophylactic anticoagulation remains unresolved.